Social Networking Sites (SNS) for Japanese Language Learning - Dewanty, Via Luviana; Farisya, Ghaida (Universitas Negeri Semarang, 2024)
Social Networking Sites (SNS) have become an integral part of modern society, influencing various aspects of life, including education. SNS facilitates interactive, collaborative, and reflective learning experiences in language learning. This study aims to evaluate the use of SNS in enhancing learning inside and outside Japanese language classrooms. The research was conducted using a qualitative approach with a survey method, utilizing a questionnaire distributed via Google Forms. Quantitative and qualitative data collected from 85 Japanese Language Education Study Program students were analyzed and presented narratively. The data were examined through the lens of SNS use in foreign language learning and its impact on language acquisition. The results reveal that most students frequently use SNS platforms such as YouTube, Instagram, and Twitter for learning Japanese, both for classroom materials and independent study. Additionally, students reported that SNS use has improved their reading, writing, listening, and speaking skills in Japanese. Moreover, SNS has been identified as a motivational tool, fostering students’ confidence in using the language orally and in writing. These findings provide valuable insights for future research on using SNS as a learning medium in Japanese language education.